2012
DOI: 10.1371/journal.pone.0034994
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Heme Oxygenase-1 on the Sensitivity of Cholangiocarcinoma Cells to Chemotherapeutic Agents

Abstract: Cancer cells acquire drug resistance via various mechanisms including enhanced cellular cytoprotective and antioxidant activities. Heme oxygenase-1 (HO-1) is a key enzyme exerting potent cytoprotection, cell proliferation and drug resistance. We aimed to investigate roles of HO-1 in human cholangiocarcinoma (CCA) cells for cytoprotection against chemotherapeutic agents. KKU-100 and KKU-M214 CCA cell lines with high and low HO-1 expression levels, respectively, were used to evaluate the sensitivity to chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 36 publications
7
63
0
Order By: Relevance
“…We have recently shown that activation of the Ras-Raf-ERK pathway promotes overexpression of HO-1 and survival of renal cancer cells (13). Induction of HO-1 in cancer is often associated with resistance of cancer cells to chemotherapeutic drugs (6,37,38); and inhibition of HO-1 in combination with chemotherapy can be a possible and effective therapeutic strategy to enhance efficiency of cancer treatment (8,10,14). In this study, we demonstrate that knockdown of HO-1 significantly augments RAPA-and sorafenib-induced apoptosis of renal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that activation of the Ras-Raf-ERK pathway promotes overexpression of HO-1 and survival of renal cancer cells (13). Induction of HO-1 in cancer is often associated with resistance of cancer cells to chemotherapeutic drugs (6,37,38); and inhibition of HO-1 in combination with chemotherapy can be a possible and effective therapeutic strategy to enhance efficiency of cancer treatment (8,10,14). In this study, we demonstrate that knockdown of HO-1 significantly augments RAPA-and sorafenib-induced apoptosis of renal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is overexpressed in different types of cancers and is further induced by radiation and chemotherapy (6,10,11). HO-1 endorses survival of various cancers, including hepatoma, melanoma, thyroid and lung carcinoma, while inhibition of HO-1 reduces viability of colon carcinoma, acute myeloid leukemia and induces apoptosis of renal cancer cells (12,13).…”
Section: Heme Oxygenase-1 (Ho-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 is the most interesting protein in terms of protecting different types of tumor cells from apoptosis, promoting their proliferation, and enhancing their invasion (Castilho et al, 2012;Kongpetch et al, 2012;Zhang et al, 2013;Furfaro et al, 2014). We previously reported that induction of HO-1 expression facilitated the growth of chronic myelocytic leukemia cells, whereas inhibition promoted their apoptosis (Chen et al, 2012;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3B). We also analyzed expression levels of HO-1 that is an enzyme responsible for physiological heme catabolism (Shibahara 2003) and also plays a cytoprotective role in cholangiocarcinoma cells (Kongpetch et al 2012). GANT61 at 10 or 20 µM induced the expression of HO-1 in HepG2 cells, HuCCT1 cells, and KKU-100 cells, which may contribute to the survival of these cancer cells.…”
Section: Differential Effects Of Gant61 On Mitf Expression In Hepaticmentioning
confidence: 99%